2009
DOI: 10.1080/17470210802618900
|View full text |Cite
|
Sign up to set email alerts
|

Short article: Size matters: Bigger is faster

Abstract: A largely unexplored aspect of lexical access in visual word recognition is "semantic size"--namely, the real-world size of an object to which a word refers. A total of 42 participants performed a lexical decision task on concrete nouns denoting either big or small objects (e.g., bookcase or teaspoon). Items were matched pairwise on relevant lexical dimensions. Participants' reaction times were reliably faster to semantically "big" versus "small" words. The results are discussed in terms of possible mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
65
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 41 publications
7
65
4
Order By: Relevance
“…For example, imageability effects in monosyllabic word-naming performance were no longer significant once AoA was controlled for (Cortese & Khanna, 2007). Likewise, the semantic size variable introduced by Sereno, O'Donnell, and Sereno (2009) did not account for variance in lexical-decision performance when correlated variables were included in the analysis with 324 words (Kang, Yap, Tse, & Kurby, 2011).…”
Section: Resultsmentioning
confidence: 98%
“…For example, imageability effects in monosyllabic word-naming performance were no longer significant once AoA was controlled for (Cortese & Khanna, 2007). Likewise, the semantic size variable introduced by Sereno, O'Donnell, and Sereno (2009) did not account for variance in lexical-decision performance when correlated variables were included in the analysis with 324 words (Kang, Yap, Tse, & Kurby, 2011).…”
Section: Resultsmentioning
confidence: 98%
“…In a lexical decision task, participants were asked to make a lexical decision on concrete nouns denoting either big or small objects. Results showed that the reaction time was faster when the words encoding a big object compared with a small object, suggesting that semantic size is automatically activated when reading a word [20]. Bottini and Casasanto [21] have also demonstrated that implicit spatial length modulates time estimates, although variations in the duration of the event nouns' referents had no effect on the judgments of the words' spatial length.…”
Section: Introductionmentioning
confidence: 99%
“… Sereno, O’Donnell, and Sereno (2009) reported that words are recognised faster in a lexical decision task when their referents are physically large rather than small, suggesting that “semantic size” might be an important variable that should be considered in visual word recognition research and modelling. We sought to replicate their size effect, but failed to find a significant latency advantage in lexical decision for “big” words (cf.…”
mentioning
confidence: 99%
“…Sereno, O’Donnell, and Sereno (2009) reported that words that refer to large objects (e.g., cathedral ) were recognised faster in a lexical decision task (LDT) than words that refer to small objects (e.g., cigarette ). Their results suggest that when a subject is deciding whether or not a letter string is a real word, there is obligatory access to the semantic size of the word (i.e., the size of the word’s referent), and that a larger semantic size facilitates processing of the word, resulting in quicker responding.…”
mentioning
confidence: 99%